Toward a Phenomenology of Place and Place-Making: Interpreting Landscape, Lifeworld and Aesthetics - Gary J. Coates; David Seamon (Oz, 1984)
Places and place-making are two significant notions in current environmental and architectural literature. Phenomenological research, which is concerned with the essential nature of human experience and consciousness, indicates that the notion of place crystallizes and focuses one essential aspect of human existence - the inescapable requirement to always be somewhere...